1999
DOI: 10.1002/(sici)1098-2744(199906)25:2<132::aid-mc8>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

p53 transactivity during in vitro osteoblast differentiation in a rat osteosarcoma cell line

Abstract: We previously demonstrated a correlation between wild-type p53 expression and appearance of osteoblastic-specific differentiation characteristics, as evidenced by basal osteocalcin gene expression in a mouse osteosarcoma tumor. The study reported here further explored the possibility of p53's having a distinct transcription-activating role in bone differentiation, in addition to its proposed role in G1 arrest and apoptosis. ROS17/2.3 osteoblastic osteosarcoma cells were stably transfected with a plasmid contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…In previous studies carried out with a murine osteosarcoma cell line showing characteristics of mature osteoblasts, we found that loss of p53 affects the ability of the cells to secrete osteocalcin, and that this property is regained after stable transfection of the cells with wild type p53 [7]. In other studies with osteoblast cell lines capable of displaying features of bone differentiation, we also observed p53 to have a distinct transcription-activating role, unrelated to growth arrest [33]. The osteocalcin promoter of p53 positive osteoblasts responded to exogenous wild type p53, and in p53 osteoblasts from knockout mice exogenous p53 had a positive effect only on cells containing at least one copy of wild type p53 [8].…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…In previous studies carried out with a murine osteosarcoma cell line showing characteristics of mature osteoblasts, we found that loss of p53 affects the ability of the cells to secrete osteocalcin, and that this property is regained after stable transfection of the cells with wild type p53 [7]. In other studies with osteoblast cell lines capable of displaying features of bone differentiation, we also observed p53 to have a distinct transcription-activating role, unrelated to growth arrest [33]. The osteocalcin promoter of p53 positive osteoblasts responded to exogenous wild type p53, and in p53 osteoblasts from knockout mice exogenous p53 had a positive effect only on cells containing at least one copy of wild type p53 [8].…”
Section: Introductionsupporting
confidence: 53%
“…We have shown decreased expression of p53 to result in an inability of osteoblasts to express osteocalcin and mineralize in vitro [7]. P53 is a transcription factor and its transcription activating activity is high during differentiation [33]. Bone matrix proteins such as osteopontin [27] and osteocalcin (5,7 and unpublished observations) have been shown to have a p53 response element within their genes and also to be regulated by p53.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations